2018
DOI: 10.1039/c8nr00348c
|View full text |Cite
|
Sign up to set email alerts
|

Co oxide nanostructures for electrocatalytic water-oxidation: effects of dimensionality and related properties

Abstract: A facile hydrothermal synthesis route was explored to obtain various nanostructures of Co oxide for applications in electrocatalytic water-splitting. The effect of reaction time and metal precursor ions on the morphology of synthesized nanostructures was studied in detail with the aid of a scanning electron microscope. By systematic optimization of the synthesis parameters, Co oxide nanostructures with single dimensionality were obtained in the form of 0D nanoparticles (NPs), 1D nanowires (NWs), 2D nanosheets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 53 publications
2
31
2
1
Order By: Relevance
“…The slope, obtained by linear fitting the plot of Δj (the difference in anodic and cathodic current densities at À 0.25 V) vs. scan rate, was employed to calculate the value of C DL . [54] Slow-scan CV with a scan rate of 2 mV s À 1 was performed in the pre-OER region to investigate the oxidation phenomenon on the catalyst surface. Faradaic efficiency (FE) tests were performed by measuring the evolved oxygen gas during a chronoamperometric test, using a bench-top NeoFox fluorometer coupled with a FOSPOR photoluminescence probe and purpose-built electrochemical cell.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…The slope, obtained by linear fitting the plot of Δj (the difference in anodic and cathodic current densities at À 0.25 V) vs. scan rate, was employed to calculate the value of C DL . [54] Slow-scan CV with a scan rate of 2 mV s À 1 was performed in the pre-OER region to investigate the oxidation phenomenon on the catalyst surface. Faradaic efficiency (FE) tests were performed by measuring the evolved oxygen gas during a chronoamperometric test, using a bench-top NeoFox fluorometer coupled with a FOSPOR photoluminescence probe and purpose-built electrochemical cell.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…In the search for NPM OER electrocatalysts, researchers have focused on a range of abundant and cheap oxides, such as nickel, iron, manganese and cobalt. [9][10][11][12][13][14][15] The OER is generally catalysed by a metal oxide rather than a pure metal, with the mechanism different for oxides with different surface morphologies. It has been reported that the OER activity of metal oxides follows the trend of NiO x > CoO x > FeO x > MnO x , 16,17 with Ni based oxides reported to exhibit the most promising OER catalysis owing to their high intrinsic activity; 18,19 In exemplifying the case of a metal surface versus a metal oxide, Babar et al 17 explored a thermally oxidized porous NiO supported on nickel foam (NF) in 1.0 M KOH towards the OER.…”
Section: Introductionmentioning
confidence: 99%
“…过渡金属氧化物不仅储量丰富, 还具有特殊的 氧化还原性质以及良好的结构稳定性, 是一类常见 的电催化电极材料 [52][53][54] , 金属氧化物/碳氮复合材 料可以通过热解 MOF 的方式获得 [55] 。钴的氧化物 具有很好的 OER 催化活性, 然而纯氧化物较差的导 电性限制了材料的性能 [56][57] , 通过与氮掺杂碳材料 复合的方式可以有效改善材料导电性差的问题, 提高 其电催化性能。 Jin 等 [58] 通过一锅式热处理的方法制备 了一种钴-钴氧化物/氮掺杂碳复合材料(CoO x @CN), 金属钴和氧化钴、具有高导电性和大比表面积的碳 以及富电子氮的协同效应是材料具有高 OER 催化 活性(260 mV@10 mA•cm -2 )的主要原因。Li 等 [59] [59] ; (b, c)CoO 以及(d, e)N-CoO 纳米线阵列的 SEM 照片 [60] ; (f)CoO/Co@N-C 的 制备过程示意图 [61] ; (g)Co 3 O 4 微球, (h)葡糖糖包覆 Co 3 O 4 微球和(i)CoO/Co@N-C 的 SEM 照片 [61] ; (j)CoO@N-C、 CoO/Co@N-C、 盐酸刻蚀处理的 CoO/Co@N-C-x 样品组(x 表示刻蚀时间)、Ir/C 以及 Pt/C 在 0.1 mol•L -1 KOH 溶液中的(j)LSV 曲线和(k)Tafel 曲线 [61] ; (l)CoO/Co@N-C 催化剂在 0.1 mol•L -1 KOH 溶液中 2000 个 CV 循环前后的 LSV 曲线 [61] Fig. 5 (a) Illustration of the synthesis process of N-Co 3 O 4 and N-CoO/C [59] ; SEM images of (b, c) CoO and (d, e) N-CoO nanowire arrays [60] ; (f) Illustration of the synthesis process of CoO/Co@N-C [61] ; SEM images of (g) Co 3 O 4 and (h) Co 3 O 4 @Glu microspheres, and (i) CoO/Co@N-C electrocatalyst [61] ; (j) LSV curves and (k) Tafel plots of CoO@N-C, CoO/Co@N-C, CoO/Co@N-C-x samples that etched in HCl with x representing etching time, Ir/C and Pt/C in 0.1 mol•L -1 KOH solution; (l) LSV curves for the CoO/Co@N-C electrocatalyst before and after 2000 CV cycles in 0.1 mol•L -1 KOH solution [61] Colorful figures are available on website 表 4 非贵金属氧化物/碳氮复合材料 OER 催化性能比较表…”
Section: 金属氧化物/碳氮复合材料unclassified